Clinical application of cinematic rendering in maxillofacial fractures. Issue 12 (December 2022) - Hu, R.; Zhang, X.-y.; Liu, J.; Wu, J.-h.; Wang, R.-p.; Zeng, X.-c.
Abstract: The purpose of this study was to evaluate the clinical application of cinematically rendered reconstructions of maxillofacial fractures. Ten surgeons and eight radiologists were shown three-dimensional images of 25 different patient cases, generated using both the volume rendering (VR) technique and the cinematic rendering (CR) technique. They were asked to mark the site of the fracture on the three-dimensional images and record the time this activity took. The effectiveness of the reconstructions to communicate with patients was assessed through the opinions of the surgeons and radiologists, as well as 25 patients. Subjective evaluations of the clinical value of the images were performed by the 18 surgeons and radiologists using a 10-item questionnaire. The percentages of correctly identified fractures of the nasal bone ( P = 0.034), fracture dislocation ( P < 0.001), and free bone fragments ( P < 0.001) were significantly higher for CR images when compared to VR images, and identification took an average of 20.81 seconds for CR and 27.48 seconds for VR ( P < 0.001). CR images were found to be more beneficial for communication with patients and scored higher for the display of fracture dislocation and free bone fragments than VR images ( P < 0.05). CR images were found to have high clinical value in the visualization of maxillofacial fractures.